Tumor Necrosis Factor and Interleukin‐6 Gene Polymorphisms and Endometriosis Risk in Asians: A Systematic Review and Meta‐Analysis. (6th December 2013) - Li, Jie; Chen, Yang; Wei, Shixiu; Wu, Hongbo; Liu, Chengjun; Huang, Qiaoying; Li, Liuming; Hu, Yanling
Summary: A relationship between endometriosis and tumor necrosis factor ( TNF‐α ) and interleukin‐6 ( IL‐6 ) gene polymorphisms has been raised for Asians. However, this topic is controversial. This study was a meta‐analysis to explore whether TNF‐α/IL‐6 gene polymorphisms were associated with a risk of endometriosis in Asians. By searching PubMed, HuGENet, and China National Knowledge Infrastructure (CNKI) databases, 17 studies were identified and included (3372 cases and 4008 controls). The odds ratio (OR) with 95% confidence interval (CI) was used to assess the association between TNF‐α/IL‐6 gene polymorphisms and endometriosis risk. An association of TNF‐α gene ‐1031T/C polymorphism with endometriosis was found ( TT + TC vs. CC : OR 0.50, 95% CI 0.30–0.82, I 2 = 37.1%, P = 0.20; TT vs. CC: OR 0.50, 95% CI 0.30–0.82, I 2 = 43.0%, P = 0.173; TC vs. CC : OR 0.49, 95% CI 0.29–0.83, I 2 = 10.6%, P = 0.327). In addition, TNF‐α‐238A/G and IL‐6 ‐174C/G gene polymorphisms were also likely to be associated with endometriosis in Asians. For the TNF‐α‐238A/G gene polymorphism, the OR was 1.577 (95% CI: 1.01–2.48). For the IL‐6 ‐174C/G gene polymorphism, the OR was 1.554 (95% CI: 1.04–2.31). No associations were detected between the TNF‐α‐308A/G and IL‐6 ‐634C/G polymorphisms and susceptibility to endometriosis. Our results indicate that the TNF‐α gene ‐1031T/C polymorphism can reduce the risk of endometriosis, but for Asians, TNF‐α‐238A/G and IL‐6 ‐174C/G gene polymorphisms may be a risk factor for endometriosis. No association was found for the TNF‐α‐308A/G and IL‐6 ‐634C/G gene polymorphisms.